Diagnostic and Metabolic Significance of Omentin-1 in Women with Hyperthyroidism and Hypothyroidism - Mahmood I. M. Alkanaani,; Lubna Samir Mohammed,; Sura Samir Mohammed,; Aseel Mokdad Hatam Abdulwahed, (American Journal of Biology and Natural Sciences, 2026)
The current study aimed to know the effect of thyroid disorders in women on the level of omentin-1 hormone and some hormones levels and compare them with the number of healthy women. This study was conducted in clinics and external laboratories in Samarra city for the period from February 2024 to May 2025.During this study, 60 samples were collected, which included 20 for women with hypothyroidism, 20 for women with hyperthyroidism, and 20 for healthy women. The ages of the women ranged between 18 and 45 years. Results showed significant hormonal and metabolic changes in women with thyroid problems compared to healthy controls. Hyperthyroid individuals had significantly higher levels of T3 and T4, and hypothyroid patients had significantly higher levels of TSH (P < 0.05). Also, lower levels of Omentin-1 were observed in hyperthyroidism and hypothyroidism groups and lowest levels were observed in hypothyroid patients. Total cholesterol, LDL-C, VLDL-C, phospholipids and fasting blood sugar levels were significantly increased (P < 0.05) in hypothyroid patients when compared to healthy controls and hyperthyroid patients. The levels of triglycerides also increased progressively in groups with thyroid disorders. The levels of HDL-C did not differ significantly across the tested groups. Correlation analysis indicated negative correlations of omentin-1 with TSH, LDL-C, total cholesterol and fasting blood sugar indicating a possible association of lower omentin-1 levels with metabolic derangement in thyroid diseases. Moreover, the ROC curve analysis revealed that omentin-1 had a good diagnostic performance for distinguishing thyroid problem patients from healthy controls with high sensitivity and specificity values. In conclusion thyroid diseases are connected with important hormonal and metabolic changes with low levels of Omentin-1, especially in case of hypothyroidism patients. The dyslipidemia detected and the increase of fasting blood sugar levels reveal a significant link between thyroid malfunction, adipokine imbalance and metabolic disruption. Furthermore, omentin-1 had a positive diagnostic performance, highlighting its potential relevance as a biomarker for thyroid diseases and their associated metabolic abnormalities.